Innovation and Growth: Why Malaysian SME Needs a New Performance Measurement System - Nor Mahirah, Mustapha; Noor Azlinna, Azizan; Sorooshian, Shahryar (2016)
A performance measurement system (PMS) has been identified by different authors since 1990, which over 20 years ago failed to satisfy the requirement of Business Process (BP) measurement. The literature shows there are lack of research discussing performance measurement in the context of business process in Small and Medium Enterprise (SME) and there is no business performance measurement system (BPMS) customized to Malaysian SME characteristics. Thus, there is a significant need to establish new BPMS for Malaysian SME. This paper emphasized the gap between performance measurement literature and SME. The authors argue that SME is not only an organization, but also business entity. Thus, the same PMS should not be used in all industries without consent about the foundation of the organization. By developing a new BPMS customized to Malaysian SME, they will have better measurement experience by measuring the right thing.